Sosialisasi Pencegahan Kekerasan Seksual pada Perempuan dalam Rangka Menciptakan Generasi Emas 2045 di SMK Kesehatan Patriot 3 Bekasi - Ridwan Hardiawan; Abdul Wahab; Yoseph Hari Bawono; Septiani Wulandari; Risna Irviana; Riana Septianti; Hesti Ratnasari; Wafiq J. Kinandy; Aditya Nugroho; Erik Himawan; Andri Sutrisno (CV. Era Digital Nusantara, 2025)
Sexual violence frequently occurs around us, and it is not experienced by women; it can also happen to men, across all professions, and throughout the human lifespan. Sexual violence can significantly impact the mental health of its victims, ultimately leading to a decline in human resource quality in the future. SMK Kesehatan Patriot 3 Bekasi is a vocational school that aims to produce reliable and trained healthcare professionals, with a majority of its students being female. Healthcare is a profession with a high risk of experiencing sexual violence. This is the motivation for us, as law students at STIH IBLAM, to address this issue as the theme of our study this semester. Our goal is to provide education and information on recognizing and identifying sexual violence, preventive measures, assertive behavior, and reporting mechanisms in the event of such incidents. This is all in the effort to contribute to the creation of a Golden Generation in 2045.